Law and Legality in the Ottoman Empire and Republic of Turkey. - Schull, Kent F. (Indiana University Press, 2016)
The editors of this volume have gathered leading scholars on the Ottoman Empire and the Republic of Turkey to chronologically examine the sweep and variety of sociolegal projects being carried in the region. These efforts intersect issues of property, gender, legal literacy, the demarcation of village boundaries, the codification of Islamic law, economic liberalism, crime and punishment, and refugee rights across the empire and the Aegean region of the Turkish Republic.